Molecular dynamics and high throughput binding free energy calculation of anti-actin anticancer drugs—New insights for better design. (October 2016) - L, Roopa.; R, Pravin Kumar.; M.M., Sudheer Mohammed
Graphical abstract: Highlights: High throughput binding free energy calculations on anti-actin anticancer drugs. Per residue energy profile was used to predict pharmachophoric sites on these drugs. Novel site for modifications and substitutions were identified in Reidispongiolide. Specific residues initiating allosteric modulations of ATP were identified in actin. Abstract: Actin cytoskeleton plays an important role in cancerous cell progression. Till date many anticancer toxins are discovered that binds to different sites of actin. Mechanism of action of these toxins varies with respect to the site where they bind to actin. Latrunculin A (LAT) binds closely to nucleotide binding site and Reidispongiolide binds to the barbed end of actin. LAT is reported to reduce the displacement of domain 2 with respect to domain 1 and allosterically modulate nucleotide exchange. On the other hand Reidispongiolide binds with the higher affinity to actin and competes with the DNaseI binding loop once the inter-monomer interaction has been formed. Evolving better actin binders being the aim of this study we conducted a comparative molecular dynamics of these two actin-drug complexes and actin complexed with ATP alone, 50 ns each. High throughput binding free energy calculations in conjugation with the high-throughput MD simulations was used to predict modifications in these two renowned anti-actin anticancer drugs for better design. Per residue energy profiling that contribute to free energy of binding shows that there is an unfavourable energy at the site where Asp157 interacts with 2-thiazolidinone moiety of LAT. Similarly, unfavourable energies are reported near macrocyclic region of Reidispongiolide specifically near carbons 7, 11 & 25 and tail region carbons 27 & 30. These predicted sites can be used for modifications and few of these are discussed in this work based on the interactions with the binding site residues. The study reveals specific interactions that are involved in the allosteric modulation of ATP by these two compounds. Glu207 closely interacting with LAT A initiates the allosteric effect on ATP binding site specifically affecting residues Asp184, Lys215 and Lys336. RGA bound actin shows high anti-correlated motions between sub domain 3 and 4. Unlike LAT A, Reidispongiolide induces a flat structure of actin which definitely should affect actin polymerisation and lead to disassembly of actin filaments.